Learning materials availability and students’ attitude as correlates of students’ performance in senior secondary school history examination in Osun State, Nigeria (2015)
The continual low performances of students in History over the years have been of grave concern to all stakeholders in education sector. This study therefore investigated availability of learning materials and attitude of students as correlates of students’ performance in senior secondary school History in Osun State. The study is a descriptive research of survey type. Multi-stage sampling technique was used and data were collected from 240 students and 30 teachers from twelve senior secondary schools in six Local Government Areas of the Osun State. Four research questions and three instruments guided the study with reliability coefficient of 0.76 for LMA; 0.67 for HAS and 0.65 for HAT respectively. Data were analysed using Pearson product moment correlation and multiple regression. Results revealed that there was positive low relationship between availability of learning materials and students' performance (r=0.33); there existed positive low correlation between students’ attitude and their performance in History (r= 0.26); both variables jointly account for 17.7% of observed variance in students’ performance in History and that availability of learning materials was more potent (B =0.37) than students' altitude (B= 0.19) in determining students' performance in History. Government should ensure constant supply of learning materials into various schools that will motivate students to have positive attitude towards history which will improve the level of students' performance in History.